Basic Technical Skill Untuk Pengembangan Kompotensi Diri di PT HAP - Indriani, Citra; Lestari, Yulian Sri (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2021)
This article will look at the extent to which the Basic Technical Skill (BTS) program has contribut-ed to the spread of admin competence at PT. HAP. By using qualitative research methods. Re-trieval and data collection is done through observation techniques. Observations were made on several employees. The goal is to find out whether the subject has occupied a position that fits the competence or not. Testing is done by selecting subjects who have participated in the Basic Tech-nical Skill (BTS) program. By looking at the change in attitude before joining the program and af-ter participating in the Basic Technical Skill (BTS) program. The results show that basic technical skills have contributed quite effectively to employee competencies, especially for the admin profes-sion, but on the one hand, basic technical skills have not contributed effectively to conflict man-agement in the company.